2020
DOI: 10.17582/journal.sja/2020/36.1.367.374
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Alternative Energy Sources of Farm Households for Cooking in Rural Areas of Peshawar

Abstract: The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of the World Health Organization concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Dotted lines on maps represent approximate border lines for which there may not yet be full agreement. The mention of specific companies or of certain manufacturers' products does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…and Sahu et al, (2020) and Singh et al, (2021) also found that the delay in sowing time caused adverse effect on plant growth by shortening the vegetative phase, creating unfavourable thermal sequence under delayed sowing with consequent effect on growth behaviour and phonological development, thereby, reducing the total biomass under delayed sowing. Similar results have also been reported by Amanullah et al, (2005) and Mohamed et al, (2017).…”
Section: Growth Characteristicssupporting
confidence: 92%
“…and Sahu et al, (2020) and Singh et al, (2021) also found that the delay in sowing time caused adverse effect on plant growth by shortening the vegetative phase, creating unfavourable thermal sequence under delayed sowing with consequent effect on growth behaviour and phonological development, thereby, reducing the total biomass under delayed sowing. Similar results have also been reported by Amanullah et al, (2005) and Mohamed et al, (2017).…”
Section: Growth Characteristicssupporting
confidence: 92%